Microstructural Effects in the Formability of Galvanneal Coatings - L' J. D. Ecuyer (The Minerals, Metals and Materials Society, 1992)
he microstructure of galvanneal coatings formed on extra low carbon and interstitial free steel substrates has been characterized using electron microscopy (TEM and SEM) and x-ray diffraction. The coatings are found to consist of a mixture of gamma, delta and zeta phases, of which delta is the main constituent. The amounts of each phase influences the powdering resistance of the coating which was evaluated using reverse Olsen testing and 60" bending. For the three heat input conditions considered, IF coatings were always found to contain a significant amount of gamma and only those which retained zeta phase on the surface exhibited a satisfactory powdering resistance. In much the same way, ELC coatings with relatively thick gamma layers performed satisfactorily only when some zeta was retained. It was also found, however, that coatings with minimal zeta and gamma had an excellent powdering resistance. The latter coatings were produced under galvannealing conditions of lower relative heat input. These results indicate that in addition to the zinc bath composition, coating weight and galvanneal thermal cycle, the base steel chemistry also has an effect on the coating microstructure. Knowledge and control of all aspects of galvannealing is therefore essential to consistently produce acceptable coatings.